Mechanism of Two-Component Mono-Oxygenases Involved in Anthracycline 1-Hydroxylation - Wandi, Benjamin Nji; Dinis, Pedro; Siitonen, Vilja; Schneider, Gunter; Schnell, Robert; Metsä-Ketelä, Mikko (American Chemical Society, 2025)
Anthracyclines are microbial natural products with important antiproliferative bioactivities that are widely used in anticancer chemotherapy. Several anthracyclines, including nogalamycin and kosinostatin, contain a 1-hydroxyl group, which is installed by an atypical two-component mono-oxygenase system. Here, we clarify the structural and mechanistic basis for 1-hydroxylation. We present the crystal structure of the NADPH-dependent reductase SwaQ2 in complex with doxorubicin, which indicates that the reaction is initiated by quinone reduction. The reduced anthracycline ligand may react with molecular oxygen, leading to the formation of a peroxide intermediate similar to flavin chemistry. The structures of the polyketide cyclase-like SnoaL2, involved in nogalamycin biosynthesis, in complex with substrate and product reveal a novel catalytic tetrad, which is used to stabilize a reduced reaction intermediate to direct the reaction toward 1-hydroxylation. Furthermore, we report the characterization of several unknown anthracycline 1-hydroxylases, which display varied substrate profiles. The structure of polyketide cyclase-like KstA15 from the kosinostatin pathway enabled structure-based protein engineering to expand the substrate specificity of the enzyme to include glycosylated anthracyclines. Our work provides insight into how reductase-hydroxylase two-component systems circumvent the need for organic cofactors or metal ions to catalyze monooxygenations in several anthracycline pathways.